Urbanization alters soil trace metal enrichment and health risks in the black soil Region of Northeast China - Guanxin Du; Yu Sun; Hongyan Lu; Baiquan Yan; Huimin Dai; Kai Liu; Keke Xu (PLoS ONE, 2026)
While urbanization is accelerating across China’s black soil regions, its specific impact on trace metal accumulation in the vulnerable urban-agricultural transition zones remains poorly understood. This study investigated such a zone in Arongqi, analyzing 32 topsoil samples (0–20 cm) from three subzones for concentrations of Cd, Cu, Pb, Zn, As, Hg, Ni, Cr, Sb, Ba, Co, Mo, Sr, V, Tl, Ag, pH, and soil organic matter (SOM). Ecological and health risks were evaluated using enrichment factors, the pollution load index (PLI), and health risk models. Pollution sources were apportioned via correlation analysis, principal component analysis, and positive matrix factorization. Results showed that urbanization did not exacerbate soil acidification but significantly reduced SOM, resulting in significant enrichment of Cd, Pb, Zn, Ba, Co, Mo, Sr, V, and Ag relative to background levels. The overall pollution status was moderate (PLI), yet distinct spatial patterns emerged: the Urbanizing Zone showed mild contamination by Cd, Ba, and Mo; the Peri-urban Arable Land by Cd, Mo, Sr, V, and Ag; and the Urban Zone by Cd, Pb, Ba, and Sr. The total carcinogenic risk was moderate for both children and adults, with higher risk for adults in the Peri-urban Arable Land and for children in the Urban Zone. Oral ingestion and dermal contact were the dominant exposure pathways, with Cr and As being the key carcinogenic factors for children and Cr also a significant risk for adults. Source apportionment identified five major contributors: traffic emissions (27.46%), soil parent material (24.77%), contemporary agricultural activities (24.54%), urban combustion (11.22%), and historical agricultural practices (11.22%). This study provides a new, spatially-resolved perspective for risk assessment and source management during the urbanization of black soil regions.